Feeding Spectrum of Vespa Orientalis Linnaeus, 1771 Under the Conditions of Southern Fergana - ugli, Adkhamjon Rasuljonov Zokhidjon (American Journal of Biology and Natural Sciences, 2025)
This study investigates the feeding spectrum of Vespa orientalis in the Southern Fergana region, focusing on the dynamics of its utilization of prey resources occurring in both natural and anthropogenic landscapes. Field surveys were conducted between 2024 and 2025 across several ecologically and agroclimatically diverse localities, including Bagdod, Rishton, Fergana District, Fergana City, and Oltiarik. Monitoring revealed that the species consistently exploits protein-rich prey groups such as flies (Musca), ants (Formicidae), lepidopteran larvae (Lepidoptera), grasshoppers (Acrididae), honey bees (Apidae), as well as other small insects. In addition, V. orientalis exhibited a strong dependence on carbohydrate-rich plant resources, with grapes, apples, pears, figs, and watermelons-known to produce sugary exudates-serving as important trophic sources. The findings demonstrate the species’ high ecological plasticity, seasonal flexibility in feeding strategies, rapid integration into natural and human-modified ecosystems, and its significant ecological role as a predator within agroecosystems.